Plan de comunicación para el fortalecimiento de la imagen de la unidad educativa Federico González Suárez del cantón Durán - Yance Jácome, Kerlly Teresa (2017)
The present research of titulación, concentrates its actions in the design of a communication plan for the Educational Unit Federico González in the Durán Canton; in the diagnosis of the situation it was determined that the main problem is the lack of positioning of the institution in the educational sector within its territory, this is presented because they do not have strategies that improve communication in the organization, it was obtained as general objective to design a communication plan for the Strengthening of its Image. It is important to note that the research consists of 4 chapters, in which several points were presented that served as a tool for the proposal; starting from the approach of the objectives of the research, the conceptualization of the subjects that served as support to the design of the strategies, a research that served to know the current situation of the image of the institution using quantitative and qualitative methods, the interpretation of the results obtained and the presentation of the proposal that will help to strengthen the image and the positioning of the educational entity. The investigation is justified due to the lack of a department or personnel in charge of the communication, since it has been handled informally causing the lack of knowledge of the identity of the institution by its teaching, administrative and students, thus generating, the lack of membership with the organization. Finally, it is concluded that the Communication Plan will benefit the Educational Unit because it will provide guidelines for the achievement of its objectives and help foster relationships among all members of the educational community.